2022
DOI: 10.2196/39727
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Internet-Based Acceptance and Commitment Therapy for Depressive Symptoms, Anxiety, Stress, Psychological Distress, and Quality of Life: Systematic Review and Meta-analysis

Abstract: Background Acceptance and commitment therapy (ACT) is an empirically supported transdiagnostic approach that involves mindfulness processes and behavior change processes for valued living. Objective This systematic review and meta-analysis of randomized controlled trials (RCTs) aimed to assess the efficacy of internet-based ACT (iACT) for depressive symptoms, anxiety, stress, psychological distress, and quality of life (QoL). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 58 publications
0
4
0
Order By: Relevance
“…When participants with at least mild depressive symptoms were included for the additional secondary analyses only ( N = 12; six per group), results showed more positive findings even with this smaller sample size, including small to medium effects of ACT on decreasing depressive symptoms ( r = 0.37), anxiety ( r = 0.40), stress ( r = 0.42), grief ( r = 0.63), and psychological inflexibility ( r = 0.51) and increasing engagement in meaningful activities ( r = 0.72) compared to the control group. A recent meta-analysis found a statistically significant larger effect of internet-based ACT on decreasing depressive symptoms when studies targeted people with depressive symptoms in particular (Han and Kim, 2022b). These findings suggest ACT may be most effective in varied mental health outcomes when caregivers are screened to target the subpopulation with depressive symptoms in particular.…”
Section: Discussionmentioning
confidence: 99%
“…When participants with at least mild depressive symptoms were included for the additional secondary analyses only ( N = 12; six per group), results showed more positive findings even with this smaller sample size, including small to medium effects of ACT on decreasing depressive symptoms ( r = 0.37), anxiety ( r = 0.40), stress ( r = 0.42), grief ( r = 0.63), and psychological inflexibility ( r = 0.51) and increasing engagement in meaningful activities ( r = 0.72) compared to the control group. A recent meta-analysis found a statistically significant larger effect of internet-based ACT on decreasing depressive symptoms when studies targeted people with depressive symptoms in particular (Han and Kim, 2022b). These findings suggest ACT may be most effective in varied mental health outcomes when caregivers are screened to target the subpopulation with depressive symptoms in particular.…”
Section: Discussionmentioning
confidence: 99%
“…In a meta-analysis on the effects of ACT in adults with chronic conditions, most of the included studies showed improvements in distress (including anxiety and depressive symptoms) following ACT compared to control conditions [78]. Han and Kim [79] investigated in the efficacy of internet-based ACT in adults on various outcomes, including stress. Like the present study, they conclude that more high-quality studies are necessary to make a firm statement.…”
Section: Discussionmentioning
confidence: 99%
“…Reappraisal (reinterpreting an event’s meaning to alter emotional responses) and suppression (inhibiting emotional behaviour) are among the most commonly studied ones (Hu et al, 2014; Troy et al, 2023; Webb et al, 2012). Acceptance, which is the willingness to experience specific emotions/situations (Carver et al, 1989), and its opposite, experiential avoidance (Boulanger et al, 2010; Gratz & Roemer, 2004), are somewhat less studied in the general population but have been largely examined among clinical samples, in part via psychotherapy research based on mindfulness as well as acceptance and commitment therapies (Han & Kim, 2022). Other strategies, like distraction, have been investigated as well, notably in the context of emotion regulation choice and goals (Millgram et al, 2019; Webb et al, 2012).…”
Section: Theoretical Frameworkmentioning
confidence: 99%